Modelos em resina: estudo de segmentos pulmonares em caes - Amanda Oliveira Paraguassú (2024)
Due to little knowledge about the canine bronchial tree according to its distribution in lung segments and lack of reports on this surgical technique as well as lobar and segmental bronchial diameter values, this present study aimed to describe the anatomical distribution of the main, lobar and segmental bronchi, and the determination of their diameters in dogs, from the creation of resin models of 15 cadaveric lung models obtained immediately or within 12 hours after death. All pieces obtained after necropsy of young dogs were used to create resin molds of the bronchial tree and subsequently analyzed following the segmental definition presented in the medical literature. The diameter of the tracheal, lobar and segmental bronchi were evaluated on thoracic radiographs and on casts, values correlated with the variables sex, size, thoracic conformation and tracheal collapse evaluated at the time of resection of the lung block. All pieces were evaluated and statistically it was observed that the accessory lobes and the cranial and caudal parts of the left cranial lobe have 2 segments; bronchial diameters are greater in animals with tracheal collapse, a factor also evaluated in the bronchi of the right middle lobe segments and the cranial part of the left cranial lobe. The diameter of the right caudal and right middle bronchi were greater in superior tracheal diameters and the diameter of the cranial part of the left cranial lobe remained with little variation in tracheal diameters of up to 18mm. It is concluded, therefore, that segmental bronchial diameters can undergo changes in the face of tracheal collapse, as well as their number when correlated with the tracheal diameter and thoracic conformation in dogs, and the chest x-ray examination can be an initial complementary examination used to bronchial-tracheal correlation.